A history of the Five Eyes Alliance: Possibility for reform and additions: A history of the Five Eyes Alliance: Possibility for reform and additions. Issue 4 (4th July 2019) - Pfluke, Corey
Abstract: At the end of World War II, the United States and the United Kingdom continued their intelligence-sharing efforts by signing the British-U.S. Communication Agreement, later renamed UKUSA. The purpose of the agreement was to streamline the intelligence-sharing process between the two nations in order to better handle global threats, most notably the Soviet Union. The addition of Canada, Australia, and New Zealand led to what is now known as the Five Eyes Alliance. Despite its global reach and close collaboration, the Five Eyes Alliance is constrained by its small membership and overburdened by current and developing global issues that need constant, up-to-date intelligence to address them. Therefore, it could be advantageous for the Five Eyes Alliance to consider expanding its membership to include Germany, France, and South Korea. This article provides a background for understanding the historical evolution of the UKUSA agreement, examining its advantages and disadvantages, before advocating for the addition of Germany, France, and South Korea to the alliance because the benefits of their membership would outweigh any potential disadvantages.